Question 13/09

Algebra Level 4

Consider the equation 3 x 2 8 x + 1 + 9 x 2 24 x 8 = 3 \sqrt{3x^2-8x+1}+\sqrt{9x^2-24x-8}=3 It is known that the largest root of the equation is k k times the smallest root. Find k k .


The answer is -9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rishabh Jain
May 17, 2016

Write the equation as: 3 x 2 8 x + 1 + 3 ( x 2 8 x + 1 ) 11 = 3 \sqrt{\color{#20A900}{3x^2-8x+1}}+\sqrt{3(\color{#20A900}{x^2-8x+1})-11}=3 Substitute 3 x 2 8 x + 1 = t \color{#20A900}{3x^2-8x+1=t} s.t eqn is:

t + 3 t 11 = 3..... ( 1 ) \large\sqrt{\color{#20A900}{t}}+\sqrt{3\color{#20A900}{t}-11}=3..... (1) Subsracting t \sqrt{ \color{#20A900}{t}} from both sides and squaring: 3 t 11 = 9 + t 6 t \large\implies 3t-11=9+t-6\sqrt{t} ( t 10 ) 2 = ( 3 t ) 2 \large\implies (\color{#20A900}{t}-10)^2=(-3\sqrt{\color{#20A900}{t}})^2 t 2 29 t + 100 = 0 \large\implies \color{#20A900}{t}^2-29\color{#20A900}{t}+100=0 t = 4 , 25 \large\implies \color{#20A900}{t}=4,25

However we can reject t = 25 \color{#20A900}{t}=25 since it doesn't satisfy original eqn ( 1 ) (1) .

Thus, t = 4 = 3 x 2 8 x + 1 \large\color{#20A900}{t}=4=\color{#20A900}{3x^2-8x+1} 3 x 2 8 x 3 = 0 \large\implies 3x^2-8x-3=0 x = 3 , 1 / 3 \large\implies x=3,-1/3 And since 3 = 9 × 1 3 3=\large{\color{#0C6AC7}{-9}}\times\frac{-1}3 hence answer is 9 \large\color{#0C6AC7}{\boxed{-9}} .

Chew-Seong Cheong
May 17, 2016

3 x 2 8 x + 1 + 9 x 2 24 x 8 = 3 3 x 2 8 x + 1 + 3 ( 3 x 2 8 x + 1 ) 11 = 3 Let y 2 = 3 x 2 8 x + 1 y 2 + 3 y 2 11 = 3 3 y 2 11 = 3 y 3 y 2 11 = y 2 6 y + 9 2 y 2 + 6 y 20 = 0 y 2 + 3 y 10 = 0 ( y + 5 ) ( y 2 ) = 0 y = { 5 ( 5 ) 2 + 3 ( 5 ) 2 11 3 rejected 2 ( 2 ) 2 + 3 ( 2 ) 2 11 = 3 accepted \begin{aligned} \sqrt{3x^2-8x+1} + \sqrt{9x^2-24x-8} & = 3 \\ \sqrt{\color{#3D99F6}{3x^2-8x+1}} + \sqrt{3(\color{#3D99F6}{3x^2-8x+1})-11} & = 3 \quad \quad \small \color{#3D99F6}{\text{Let }y^2 = 3x^2-8x+1} \\ \implies \sqrt{\color{#3D99F6}{y^2}} + \sqrt{3\color{#3D99F6}{y^2}-11} & = 3 \\ \sqrt{3y^2-11} & = 3 - y \\ 3y^2 - 11 & = y^2 - 6y + 9 \\ 2y^2 + 6 y - 20 & = 0 \\ y^2 + 3 y - 10 & = 0 \\ (y+5)(y-2) & = 0 \\ \implies y & = \begin{cases} \color{#D61F06}{-5} & \color{#D61F06}{\implies \sqrt{(-5)^2} + \sqrt{3(-5)^2-11} \ne 3} & \color{#D61F06}{\text{rejected}} \\ \color{#3D99F6}{2} & \color{#3D99F6}{\implies \sqrt{(2)^2} + \sqrt{3(2)^2-11} = 3} & \color{#3D99F6}{\text{accepted}} \end{cases} \end{aligned}

3 x 2 8 x + 1 = y 2 = 4 3 x 2 8 x 3 = 0 ( 3 x + 1 ) ( x 3 ) = 0 x = { 1 3 3 k = 3 1 3 = 9 \begin{aligned} \implies 3x^2-8x+1 & = y^2 = 4 \\ 3x^2-8x-3 & = 0 \\ (3x+1)(x-3) & = 0 \\ \implies x & = \begin{cases} -\frac{1}{3} \\ 3 \end{cases} \\ \implies k & = \frac{3}{-\frac{1}{3}} = \boxed{- 9} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...